Analysis of liquid sloshing frequencies in a partially filled 3Dd rectangular tank - Kumar, Narveen; Choudhary, Neelam (Zielona Góra: Uniwersytet Zielonogórski)
This research investigates liquid sloshing in a 3D rigid rectangular tank. The impact of rigid baffle on sloshing frequencies has been studied. The mathematical model has been developed using potential theory. The boundary value problem has an analytical solution in terms of velocity potential with undetermined frequency. We get a system of homogeneous algebraic equations using boundary and free surface conditions. The frequencies are calculated using the non-trivial solution condition. Frequencies of baffled tank are computed for various filling levels. The effects of filling level on frequencies are identified. ANSYS software is used to report the liquid domain and rigid baffle mode forms.
Keywords: frequency; rectangular tank; rigid baffle; sloshing mitigation